A critical evaluation of the effectiveness of international joint ventures in enhancing performance of an entity: a case of RSC-Steelforce (Pvt) Ltd - Mano, Talent (Midlands State University, 2019)
This study’s main objective is to critically evaluate the effectiveness of engaging into an international joint venture with the aim of enhancing or improving the profitability together with the overall performance of an entity. At the end of 2015 Reinforce Steel Contractor and Steelforce got into an international joint venture with the aim of increasing revenue collection, reducing cost and sharing risk, improving profits, creating economies of scale, cost synergies, effective management of interdependence and strengthening of the capital intensity, preempting competition, assessing new technology and accessing new customers thus expanding revenue streams. However, in the post international joint venture era the entity witnessed slight decrease in costs and premature increase in revenues and profits not achieving the targeted profit revenue and cost which raised eyebrows on the effectiveness of international joint venture in enhancing performance. In the study a descriptive research design was used in data collection and primary data was collected through questionnaires and interviews and secondary data was attained from the company financial statements. The population samples comprising of thirty-six employees were drawn from RSC-Steelforce (Pvt) Ltd and the stratified random sampling technique was used to come up with a sample. The study unveiled that the entity is enjoying some competitive advantages through the acquisition of highly technical machines, increase in market power, gaining of purchasing power through discounts and charging of low prices. The challenges being faced by the company include inadequate defined operational interfaces with the parents, lack of communication and coordination amongst its departments. Recommendations were suggested which include the implementation of training programs that facilitate knowledge and skills sharing amongst employees and adopting a variety of technological services and accounting programs to cater for the ever-changing customer tastes and preferences.